A comparison of Y-chromosomal lineage dating using either resequencing or Y-SNP plus Y-STR genotyping() - Wei, Wei (Elsevier, 2013)
We have compared phylogenies and time estimates for Y-chromosomal lineages based on resequencing ∼9 Mb of DNA and applying the program GENETREE to similar analyses based on the more standard approach of genotyping 26 Y-SNPs plus 21 Y-STRs and applying the programs NETWORK and BATWING. We find that deep phylogenetic structure is not adequately reconstructed after Y-SNP plus Y-STR genotyping, and that times estimated using observed Y-STR mutation rates are several-fold too recent. In contrast, an evolutionary mutation rate gives times that are more similar to the resequencing data. In principle, systematic comparisons of this kind can in future studies be used to identify the combinations of Y-SNP and Y-STR markers, and time estimation methodologies, that correspond best to resequencing data.